Semiconductor elastic medium with electromagnetic porosity, photothermal excitation, and the Thomson effect - Alhejaili, Weaam; Elamin, Mahjoub A.; Chtioui, Houda; Chteoui, Riadh; El-Bary, Alaa A.; Anwer, N.; Tantawi, Ramdan S.; Lotfy, Kh. (Frontiers in Physics, 2023)
The Thomson influence on semiconductors can be studied by investigating the connection between the presence of thermoelectric and magnetic fields and porosity and the photothermal transport mechanism. Elastic waves, voids, magnetic fields, and thermoelectric effects in plasma are investigated. The governing equations were analyzed for a uniformly distributed and isotropic medium under two-dimensional [electronic and elastic (plasmaelastic)] deformations. The charge density is considered solely dependent on the induced electric current over time. The Laplace-Fourier transforms method in two dimensions is employed to obtain solutions for the primary variables. The recombination process results in the application of electro-mechanical loads and thermal effects on the free surface of a porous medium. The Laplace-Fourier transformations inversion operations help obtain comprehensive solutions in this study. The effects of porosity parameters and silicon (Si) on a semiconductor porous material are considered, and the resulting physical field distributions are analyzed and represented graphically.